ANDROID-BASED INTRODUCTION APPLICATION OF MEDICINAL PLANTS - Rinawati Rinawati; Sri Hartati; Anggi Firmanto (SRA Publishing, 2021)
Medicinal plants are very abundant biological wealth in Indonesia. Herbs made from medicinal gardens have also become the heritage of the Indonesian people. In the development of technology in the current era, especially for developers, a lot of the latest innovations have emerged. One of them is making the introduction application of this medicinal plant. However, currently there are still many people who have not used IT, so this research needs to be done not only once in order to create a more effective and updated application according to their needs. This research was conducted to create an android-based introduction application of medicinal plants which is simpler than previous research. This research was made using the mitt app inventor which is obtained for free and is easy to use because it has provided coding according to what researcher needs. This research model used the Systems Development Life Cycle (SDLC). From this research, the researcher produced an application which can be used to find out the list of plants, the benefits of plants and types of traditional medicinal plants which can treat certain types of diseases.